PENGARUH SUKU BUNGA, STRUKTUR MODAL, UKURAN PERUSAHAAN DAN KEPEMILIKAN MANAJERIAL TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN FOOD AND BEVERAGE YANG TERDAFTAR DI BURSA EFEK INDONESIA - Intan Putri Suryati; Desi Fitria; Ahmad Junaidi; Mirra Sri Wahyuni (Jurnal Akuntansi, Keuangan dan Teknologi Informasi Akuntansi, 2026)
This study aims to analyze the effect of interest rates, capital structure, firm size, and managerial ownership on firm value in food and beverage companies listed on the Indonesia Stock Exchange for the 2020–2024 period. The research method employed is quantitative, utilizing secondary data in the form of company annual reports. The population in this study was food and beverage companies listed on the Indonesia Stock Exchange. The sampling technique used purposive sampling, resulting in 28 companies with a total of 140 observations during the study period. Data analysis was performed using multiple linear regression with the assistance of statistical applications. The results show that interest rates have no significant effect on firm value, capital structure has no significant effect on firm value, firm size has a negative and significant effect on firm value, while managerial ownership has no significant effect on firm value. The conclusion of this study indicates that internal and external factors have different influences on firm value. Firm size is the only variable shown to influence firm value in food and beverage companies listed on the Indonesia Stock Exchange, while interest rates, capital structure, and managerial ownership have not significantly influenced changes in firm value during the study period. Keywords: Managerial Ownership, Firm Value, Capital Structure, Interest Rate, Firm Size